2005
DOI: 10.1146/annurev.anthro.34.081804.120412
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Market Economies on the Well-Being of Indigenous Peoples and on Their Use of Renewable Natural Resources

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Annual Reviews is collaborating with JSTOR to digitize, preserve and extend access to Annual Review of Anthropology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
167
1
18

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(199 citation statements)
references
References 76 publications
6
167
1
18
Order By: Relevance
“…Although many studies have found MI to be associated with rapid deterioration of cardiovascular and metabolic health, our results are similar to several other studies in their findings of mixed health outcomes (Berry et al 1986;Godoy et al 2005;Sorensen et al 2005;Steffen et al 2006). Whether MI has a positive or negative effect on health instead depends on local conditions and factors such as the character, intensity and duration of MI, the existing health and diet of the population prior to MI, biological factors that shape susceptibility to health problems and cultural factors that influence behaviour.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although many studies have found MI to be associated with rapid deterioration of cardiovascular and metabolic health, our results are similar to several other studies in their findings of mixed health outcomes (Berry et al 1986;Godoy et al 2005;Sorensen et al 2005;Steffen et al 2006). Whether MI has a positive or negative effect on health instead depends on local conditions and factors such as the character, intensity and duration of MI, the existing health and diet of the population prior to MI, biological factors that shape susceptibility to health problems and cultural factors that influence behaviour.…”
Section: Discussionsupporting
confidence: 92%
“…Although debate exists over how best to conceptualize and operationalize MI (Dressler and Bindon 2000;McDade 2002;Godoy et al 2005;Lu 2007;Sorensen et al 2009;McDade and Nyberg 2010), this process involves the emergence of market-based systems of exchange and, specifically, the increased degree of participation in and dependence on markets to obtain food resources (Godoy 2001;Godoy and Cardenas 2000;Godoy et al 2005;Lu 2007). The transition from a subsistence-based lifestyle to a market economy influences myriad dimensions of life (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indigenous people along the Yukon River hunt, fish, gather, and share their harvest to provide for their families and community (AJS and CATG 2010). Throughout the course of Indigenous people's existence in the Alaskan Arctic there has been much ecological and social change due, primarily, to climate change and inflexible management policies and systems born from extractionist economies (Williams et al 2016;Godoy 2005;Goldsmith 2010). Alaska Natives have gone from a system of natural resources stewardship built on varying scales of relational experiences and observations over thousands of years with the natural environment (Williams et al 2016), to a system that is inflexible and young, merely 60 years old in Alaska.…”
Section: Resultsmentioning
confidence: 99%
“…8 The notion of "traditional knowledge" has since followed its own developmental path, with a strong environmental focus. Many authors use the two conceptstraditional and indigenous -interchangeably (Godoy et al, 2005).As for Latin America, the local history of all these notions is not very different. The term "indigenous knowledge" appeared very early on and spread primarily through Brazil, Mexico, Bolivia and Chile.…”
mentioning
confidence: 99%